2008
DOI: 10.1111/j.1600-0463.2008.125m2.x
|View full text |Cite
|
Sign up to set email alerts
|

Canine neoplasia – Introductory paper

Abstract: The paper gives a brief introduction to canine oncology, including its comparative aspects as basis for recording tumours in the animal kingdom. In an abbreviated presentation of the Norwegian Canine Cancer Project for the years 1990 – 1998, the data (n=14,401) were divided into age groups, each of two years, into different categories of tumours, and into age and gender. As expected, cutaneous histiocytoma was the dominant tumour type in both sexes during the two first years of life. In the age group 2 – 3.99 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
42
1
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 37 publications
6
42
1
3
Order By: Relevance
“…This is consistent with other studies that evaluate the general dog-population, such as the one in Denmark [19] and Norway [18,35]. However the EIR calculated for MCT in both of the data-sets is much higher in relation to the EIR of MCT in dogs irrespective of breed than would be expected on the basis of previous reports [34].…”
Section: Estimated Incidence Ratessupporting
confidence: 91%
See 2 more Smart Citations
“…This is consistent with other studies that evaluate the general dog-population, such as the one in Denmark [19] and Norway [18,35]. However the EIR calculated for MCT in both of the data-sets is much higher in relation to the EIR of MCT in dogs irrespective of breed than would be expected on the basis of previous reports [34].…”
Section: Estimated Incidence Ratessupporting
confidence: 91%
“…Future research should examine this in more detail, since it influences the level of veterinary care and will also influence epidemiological studies. The percentage of malignant tumours as well as its EIR in the tumours diagnosed using histopathology in the current study were higher than what has been reported in other studies that considered the general dog-population; namely in Norway (2008) [18] Italy (2009) [30,31] and Alameda (1968) [32,33]. This is suggestive of a general breed-predisposition for malignant tumours in the Golden retriever.…”
Section: Estimated Incidence Ratescontrasting
confidence: 77%
See 1 more Smart Citation
“…There has been a growing concern in recent decades about the understanding and characterization of spontaneous neoplasms in domestic and wild animals, with an increase in research in comparative oncology, mainly due to the need of development of biological systems for environmental monitoring (4). In African hedgehogs, spontaneous tumors have been frequently reported, and a retrospective necropsy study reported 30% of prevalence of spontaneous neoplasms in this species (13).…”
Section: Discussionmentioning
confidence: 99%
“…Males suffered also from testicles and skin cancer. Comparative research conducted in the same study showed that the mammary and testicular neoplasia seemed to be more frequent in dogs than in humans, while intestinal, pulmonary and prostatic malignancies were less common in dogs, each of them was under 1% of total (Gamlem et al 2008).…”
mentioning
confidence: 90%